2014
DOI: 10.1002/etc.2634
|View full text |Cite
|
Sign up to set email alerts
|

Trophodynamics of current use pesticides and ecological relationships in the Bathurst region vegetation‐caribou‐wolf food chain of the Canadian Arctic

Abstract: The bioaccumulation of current use pesticides (CUPs) and stable isotopes of carbon and nitrogen were investigated in vegetation-caribou-wolf food chain in the Bathurst region (Nunavut, Canada). Volumetric bioconcentration factors (BCF(v)) in vegetation were generally greatest for dacthal (10-12) ≥ endosulfan sulfate (10-11) > ß-endosulfan (>9.0-9.7) ≥ pentachloronitrobenzene (PCNB; 8.4-9.6) > α-endosulfan (8.3-9.3) > chlorpyrifos (8.0-8.7) >chlorothalonil (7.6-8.3). The BCF(v) values in vegetation were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 44 publications
2
35
3
Order By: Relevance
“…and Flavocetraria sp.) and moss ( Rhytidium rugosum ), which are rootless, atmospherically dependent primary producers, had Σendosulfan profiles that were nearly identical to air . The differences in proportions of Σendosulfan in plankton between locations did however reflect the differences in water, with uptake and accumulation in plankton and algae apparently in proportion to endosulfan availability in seawater at each location (Figure ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…and Flavocetraria sp.) and moss ( Rhytidium rugosum ), which are rootless, atmospherically dependent primary producers, had Σendosulfan profiles that were nearly identical to air . The differences in proportions of Σendosulfan in plankton between locations did however reflect the differences in water, with uptake and accumulation in plankton and algae apparently in proportion to endosulfan availability in seawater at each location (Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…Extracts were analyzed by gas chromatography, negative chemical ionization, low‐resolution mass spectrometry (GC‐NCI‐MS). The GC‐MS parameters, analyses, and quantification methods are identical to those previously reported and are briefly outlined in the Supplemental Data. Mass to charge ( m / z ) ratios of ion fragments monitored for each compound are included in Supplemental Data, Table S2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to high stability and long-range transportation characteristics, POPs find their ways from water and air into the soil ecosystem where they are taken up by plants and living organisms (Hao et al 2014;McLeod et al 2014;Morris et al 2014). They follow the usual process of bioaccumulation and biomagnification as they move up in each trophic level of the food chain.…”
Section: Pops In the Environmentmentioning
confidence: 99%
“…Only one study was found on movement of CPY in food webs. Several current-use pesticides were measured in a terrestrial food web in the Canadian Arctic [97], and CPY was detected frequently in moss and mushrooms (83% to 86%) but at lesser frequency in lichens, willow, and grass (44% to 50%). Concentrations ranged from 0.87 ng/g l. ms. in moss to 0.07 ng/g l. ms. in lichen.…”
Section: Trophic Magnificationmentioning
confidence: 99%